2007
DOI: 10.1016/j.ccr.2006.11.023
|View full text |Cite
|
Sign up to set email alerts
|

High TGFβ-Smad Activity Confers Poor Prognosis in Glioma Patients and Promotes Cell Proliferation Depending on the Methylation of the PDGF-B Gene

Abstract: TGFbeta acts as a tumor suppressor in normal epithelial cells and early-stage tumors and becomes an oncogenic factor in advanced tumors. The molecular mechanisms involved in the malignant function of TGFbeta are not fully elucidated. We demonstrate that high TGFbeta-Smad activity is present in aggressive, highly proliferative gliomas and confers poor prognosis in patients with glioma. We discern the mechanisms and molecular determinants of the TGFbeta oncogenic response with a transcriptomic approach and by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
400
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(435 citation statements)
references
References 34 publications
24
400
1
Order By: Relevance
“…In particular in GBM, we observed that some tumors show aberrantly high TGFβ activity and this correlated with poor prognosis ( 16 ). The presence of extremely high TGFβ activity in the most-aggressive tumors suggests that TGFβ may confer a selective advantage to the tumor and, hence, the inhibition of the TGFβ pathway might exhibit an antitumoral effect.…”
Section: Discussionmentioning
confidence: 80%
“…In particular in GBM, we observed that some tumors show aberrantly high TGFβ activity and this correlated with poor prognosis ( 16 ). The presence of extremely high TGFβ activity in the most-aggressive tumors suggests that TGFβ may confer a selective advantage to the tumor and, hence, the inhibition of the TGFβ pathway might exhibit an antitumoral effect.…”
Section: Discussionmentioning
confidence: 80%
“…Exposure to the AhR antagonist CH-223191 proved to be a reliable measure to decrease the levels of TGF-b and LTBP-1 in glioma cells and, as the important functional readout, cellular pSmad2 levels (Figures 4 and 5). The latter have been characterized as a striking negative prognosticator in human glioma patients (Bruna et al, 2007). Conversely, constitutive overexpression of CA-AhR in LNT-229 cells led to an increase of LTBP-1 and TGF-b2 protein levels, resulting in enhanced intracellular TGF-b signaling as indicated by increased pSmad2 levels ( Figure 5b) and enhanced TGF-b reporter activity (Figure 5c).…”
Section: Discussionmentioning
confidence: 92%
“…This tumor type is highly lethal with a median survival of 7-9 months in population-based studies (Ohgaki et al, 2004). High transforming growth factor-b (TGF-b)/Smad activity is typical for these aggressive tumors and confers a poor prognosis (Bruna et al, 2007). Depleting TGF-b by RNA interference or antagonizing the TGF-b receptor I kinase, which mediates Smad2 signaling, both inhibit growth and invasiveness and enhance the immunogenicity of murine and human glioma cells in vitro and in vivo (Friese et al, 2004;Uhl et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b can act as both a potent tumour suppressor and a potent promoter of metastasis in a context-dependent manner, but a molecular understanding of how and when TGF-b acts in a pro-oncogenic manner is limited (Pardali and Moustakas, 2007). Recent data indicate that this may involve Smad activation, and in the case of glioma (Bruna et al, 2007) and breast cancer (Kang et al, 2005), high Smad activity correlates with poor prognosis. It has earlier been proposed that TGF-b-mediated regulation of non-Smad pathways may also contribute to the pro-oncogenic actions of TGF-b (Wakefield and Roberts, 2002;Roberts and Wakefield, 2003).…”
Section: Discussionmentioning
confidence: 99%